2013
DOI: 10.3109/07420528.2013.793196
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Artificial Dawn and Morning Blue Light on Daytime Cognitive Performance, Well-being, Cortisol and Melatonin Levels

Abstract: Light exposure elicits numerous effects on human physiology and behavior, such as better cognitive performance and mood. Here we investigated the role of morning light exposure as a countermeasure for impaired cognitive performance and mood under sleep restriction (SR). Seventeen participants took part of a 48h laboratory protocol, during which three different light settings (separated by 2 wks) were administered each morning after two 6-h sleep restriction nights: a blue monochromatic LED (light-emitting diod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
99
2
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 134 publications
(113 citation statements)
references
References 53 publications
10
99
2
2
Order By: Relevance
“…Our results corroborate our previous analysis that artificial morning dawn simulation light improves subjective perception of well-being and mood, as well as cognitive performance across the day under conditions of mild sleep restriction [14]. However, here we showed that the light effect on performance depends on the investigated cognitive domain, suggesting that different pathways may be implicated in this effect.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our results corroborate our previous analysis that artificial morning dawn simulation light improves subjective perception of well-being and mood, as well as cognitive performance across the day under conditions of mild sleep restriction [14]. However, here we showed that the light effect on performance depends on the investigated cognitive domain, suggesting that different pathways may be implicated in this effect.…”
Section: Discussionsupporting
confidence: 92%
“…Evidence for the latter arises from studies in which daytime performance increased after 30 min from light onset [30,31], from an fMRI study in which daytime light enhanced cognitive brain activity during an oddball task [32] and from our previous analysis in which morning light exposure (dawn simulation light) increased wellbeing and enhanced performances across the day [14]. Recently, another study showed the critical role of light for cognitive brain responses in emphasizing the evidence of a cognitive role for melanopsin, which may confer a form of "photic memory" to human cognitive brain function [33].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations